Analisis Kesalahan Siswa Kelas VII dalam Menyelesaikan Soal Geometri - Hadiyanto, Fahrur Rozi (FKIP Universitas Mataram, 2020)
Triangle and rectangle are material taught at the junior high school level. However, there are still many students who make mistakes in solving geometry problems. This can be a reference to find out what are difficulties experienced by students. The purpose of this study is to find out the types and causes of student errors in solving geometry problems. This research uses a qualitative approach. The subjects in this study were 3 students of class VII A MTs Surya Buana Malang. The results showed that the types of errors made by students were concept errors, procedural errors, and errors in understanding the questions. Concept errors made by students were errors in the types of triangle, properties of quadrilateral shapes, definitions of quadrilateral, concepts of operations on number, concepts of circumference, area of triangle and area of rectangle. Procedural errors made by students were mistakes in giving unit of perimeter or area, calculation, and understanding the problem. The causes of the error were students not being able to distinguish between angle and line segment, not being able to distinguish types of triangle based on angle and side, not being able to understand the concept of number operations, lacking accuracy, not understanding the difference in area and number of angle in triangle, lack of variation in questions given by the teacher, and lack of understanding about perimeter and area of the quadrilateral.ÃƒÂ‚Ã‚Â AbstrakSegitiga dan segiempat merupakan materi yang diajarkan pada tingkat SMP. Akan tetapi, masih banyak siswa yang melakukan kesalahan dalam menyelesaikan soal geometri. Hal ini dapat menjadi acuan untuk mengetahui kesulitan apa saja yang dialami siswa. Tujuan dari penelitian ini adalah untuk mengetahui jenis dan penyebab kesalahan siswa dalam menyelesaikan soal geometri. Penelitian ini menggunakan pendekatan kualitatif. Subjek penelitian ini adalah 3 dari 33 siswa kelas VII A MTs Surya Buana Malang. Hasil penelitian menunjukkan bahwaÃƒÂ‚Ã‚Â jenis kesalahan yang dilakukan siswa meliputi: kesalahan konsep, kesalahan prosedur, dan kesalahan dalam memahami soal. Kesalahan konsep yang dilakukan oleh siswa meliputi: kesalahan jenis segitiga, sifat-sifat bangun segiempat, definisi segiempat, konsep operasi pada bilangan, konsep keliling dan luas segitiga dan segiempat. Kesalahan prosedural yang dilakukan oleh siswa adalah kesalahan pemberian satuan keliling atau luas dan kesalahan perhitungan. Kesalahan lain yakni dalam memahami soal. Sedangkan penyebab kesalahan tersebut antara lain siswa belum mampu membedakan antara sudut dan ruas garis, belum mampu membedakan jenis segitiga berdasarkan sudut dan berdasarkan sisi, belum mampu memahami konsep operasi bilangan, kurang teliti, belum memahami perbedaan luas dan jumlah sudut dalam segitiga, kurangnya variasi soal yang diberikan guru, dan kurang memahami keliling dan luas segiempat